Rheumatoid arthritis and gastroesophageal reflux disease: a bidirectional and multivariable two-sample Mendelian randomization study - Wang, Haifan; Chen, Zhihao; Dang, Xiaoqian; Wang, Haoyu (Frontiers in Genetics, 2023)
Aims/hypothesis: The association between Gastroesophageal Reflux Disease (GERD) and Rheumatoid Arthritis (RA) has been reported by many observational studies in the Asian population. Here, we examined the bidirectional causal effects between GERD and RA by two sample MR analyses using genetic evidence.Methods: Two-sample Mendelian randomization analyses were performed to determine the causal effect of the GERD (129080 cases vs 602604 control participants) on RA (6236 cases vs 147221 control participants) and RA on GERD respectively. The inverse-variance weighted (IVW) method was used as the primary analysis. Weighted median and MR-Egger regression were taken as supplements. The Cochran Q test evaluated the heterogeneity. Horizontal pleiotropy was detected by estimating the intercept term of MR-Egger regression. Further, multivariable MR analyses were performed to exclude the influence of confounding factors including years of schooling, BMI, and time spent watching television between GERD and RA.Result: Both The univariate MR (UVMR) and multivariable MR (MVMR) provided validsstrong evidence that the RA was causally and positively influenced by GERD (UVMR: